Relationship Between Peak Ground Acceleration and Modified Mercalli Intensity in Costa Rica - Linkimer, Lepolt (Universidad de Costa Rica, 2007)
The first relationship between Modified Mercalli Intensity (MMI) scale and the horizontal component of Peak Ground Acceleration (PGA) was developed for the Costa Rican region using regression analysis of 108 earthquakes (2.8 < Mw < 7.7) that occurred between 1983 and 2004. For each PGA instrumentally recorded, a single MMI value was assigned based on the geographic proximity to the PGA observation. A total of 330 values of both the largest PGA of the two horizontal components (PGAmax) and the average of the two horizontal components (PGAave) were associated to MMI values. The correlations obtained are: MMI=2.30log(PGAmax)+0.92 and MMI=2.33log(PGAave)+0.76 for MMI II-V and MMI=3.82log(PGAmax)-1.78 and MMI=4.60log(PGAave)-3.38 for MMI V-VII. Predicted PGA intervals for each intensity unit were proposed based on these equations. There is a fairly remarkable agreement between the PGAmax vs. MMI found in this study and the correlation calculated by Wald et al. (1999a) for California. Keywords: Modified